Episcopal networks and authority in late antique Egypt : bishops of the Theban region at work - Dekker, Renate, 1983- (Orientalia Lovaniensia analecta, 2018)
"In this book the author examines how two bishops in the Theban region contributed to the rise of a new, anti-Chalcedonian church hierarchy, which became the forerunner of the Coptic Orthodox Church. Abraham of Hermonthis (ca. 590-621) and Pesynthius of Koptos (599-632) are exceptional, since a large number of their professional documents (mostly in Coptic) is preserved. By applying Social Network Analysis to these documents, the author reconstructed their individual social networks and linked them to a wider regional network that was centered on monastic communities in Western Thebes (west of modern Luxor), but also included a large number of civil officials, clergymen and lay men and women. In addition, a social model of episcopal authority was adopted, in order to evaluate how the bishops used their authority and to explain what made Pesynthius so extraordinary that he is still remembered as a saint by the Coptic Orthodox Church"-- Publisher's website.